EMBRACING SMART ORTHODONTICS: 3D–BASED CUSTOM TEMPORARY ANCHORAGE DEVICES (TADS) FOR EFFICIENT MALOCCLUSION MANAGEMENTS - Brian Limantoro (Lux Mensana: Journal of Scientific Health, 2025)
Introduction. Malocclusion, a common dental condition characterized by misalignment of teeth and jaws, has significant implications for masticatory function, periodontal health, and facial aesthetics. Temporary Anchorage Devices (TADs) have been widely utilized in orthodontics to enhance treatment stability and control complex tooth movements. However, variations in patient anatomy and the limitations of conventional TADs placement contribute to a 15–20% failure rate, underscoring the need for improved precision and customization. Objective this study reviews the potential of three–dimensional (3D) customized TADs as an innovative approach to achieve superior accuracy, stability, and efficiency in managing diverse malocclusion cases. Methods: A comprehensive literature review was conducted using PubMed, ScienceDirect, SCOPUS, Medline, ProQuest, and EBSCO databases. Twenty–three peer–reviewed articles published between 2019 and 2024 were analyzed, focusing on 3D–based TADs customization systems, their mechanical workflows, and their clinical efficacy in orthodontic treatment optimization. Result & Analysis. The 3D–based customization of TADs involves a digital workflow integrating CBCT and intraoral scanning, CAD design, finite element method (FEM) validation, and 3D printing through stereolithography (SLA), selective laser sintering (SLS), or direct metal laser sintering (DMLS). This technology enables highly individualized designs and guided insertion techniques, enhancing anchorage precision and reducing procedural errors. Evidence from systematic reviews indicates that 3D–guided TADs achieve higher accuracy and stability, with reduced failure rates compared to conventional methods. Furthermore, personalized TAD fabrication minimizes patient discomfort, enhances compliance, and shortens treatment duration. Discussion: The integration of 3D printing technology in TADs design marks a significant breakthrough in orthodontic practice. By providing precise, patient–specific devices and guided placement systems, 3D customized TADs improve clinical outcomes, minimize complications, and advance minimally invasive orthodontic care. Their adoption represents a vital step toward personalized and technologically advanced orthodontic treatment strategies.